Application of Medical Image Artificial Intelligence in Medical Diagnosis and Treatment - Wang, Yunhan (International Journal of Computer Science and Information Technology, 2024)
With the progress of science and technology, artificial intelligence has made remarkable progress in various fields. Among them, the application of medical imaging is an important branch of AI technology. The purpose of this paper is to enhance the precision, efficiency and accuracy of medical image analysis. The research methods chiefly include deep learning, machine vision and natural language understanding. Through reading this article, we can know that the application of artificial intelligence in medical screenage diagnosis has a wide range of application prospects, but also faces some challenges. With continued research and development, we can expect to see more AI playing a role in medical imaging and bringing more benefits to human health.